The Political Economy of Regional Cooperation in South Asia - V.V. Desai (Asian Development Bank (ADB), 2010)
Regional cooperation arrangements (RCAs) have produced vastly dissimilar performances; some have spurred remarkable expansion in trade and cooperation among members, while several others have achieved little. Studies show that performances vary because RCAs differ from one another in important characteristics, namely the (i) objectives they aim to achieve, (ii) balance of power among member states, and (iii) political structures and processes of decision-making within individual member states. Subject characteristics uniquely influence and condition the functioning of RCAs. An assessment of the performance of the South Asian Association for Regional Cooperation (SAARC) reveals that the extremely skewed balance of power within the region and antagonistic inter-state relations among member states have stunted the organization's effectiveness. To reverse the situation, SAARC's member countries need to repair the prevailing atmosphere of distrust and suspicion, and build cordial inter-state relations. They also need to empower the SAARC Secretariat to function as a competent and neutral facilitator of cooperation in South Asia.
hdl:11540/1946
Keywords: F53; F59; 330; South Asia; regional cooperation arrangements; South Asian Association for Regional Cooperation; SAARC; political economy; trade; economic integration